The Development of Using E-Procurement System in Private Sector - Tangwiriyasakul, Phakhanat; Thitiluck, Dhachakorn (Journal of Dhamma for Life, 2026)
The study titled The Development of Using E-Procurement System in the Private Sector employed a qualitative research method. The objectives were: to study the E-Procurement system used in procurement; to examine the advantages, disadvantages, and problems associated with the use of the E-Procurement system as experienced by the private sector in relation to both government and private sector transactions; and to suggest improvements for the use of the E-Procurement system within the private sector. The research was conducted using document analysis and in-depth interviews. Participants included 16 key informants, all private entrepreneurs operating in the construction industry who supply products to the private sector. The results of the study revealed that the two most commonly used bidding methods within the E-Procurement system are: 1) the electronic bidding method (e-bidding), and 2) the e-auction method. The analysis identified two key perspectives regarding the advantages, disadvantages, and challenges of using the E-Procurement system: first, the advantages the private sector holds over the government sector; and second, the advantages that one private sector entity may have over another. In addition, the study suggests that one of the primary problems in procurement is corruption, which often stems from a lack of transparency. While the E-Procurement system can help address corruption to some extent by increasing transparency and accountability, it may not be able to eliminate the issue entirely.